Efficiency Analysis of Turkish Container Ports: SFA or DEA? - İsmail Yenilmez (Verimlilik Dergisi)
Purpose: The study compares the efficiency of Turkish container ports using Stochastic Frontier Analysis and Data Envelopment Analysis. It aims to provide comparative insights for enhancing ports' operational performance. Capacity utilization and operational performance were analyzed in detail through ratio analysis.Methodology: Two efficiency measurement techniques were employed: SFA evaluates efficiency by accounting for random errors and external factors, while DEA assesses relative efficiency by comparing ports to the best performers. Ratio analysis was used to evaluate capacity utilization through current handling capacity and annual growth rates.Findings: Significant differences were observed between SFA and DEA results. Ports like MIP MERSİN and EVYAP demonstrated high efficiency in both methods, while discrepancies were detected in ports like MARDAŞ and ÇELEBİ BANDIRMA. SFA better captures external factors and operational challenges, whereas DEA emphasizes relative efficiency. For instance, MARDAŞ exhibited rapid growth in handling volume but low operational efficiency. Ratio analysis showed varying capacity utilization levels, with some ports operating near full capacity, while others, like AKÇANSA, operate at low capacity and need operational improvements.Originality: The study provides a holistic view of port efficiency by integrating SFA, DEA, and ratio analysis. It not only measures comparative efficiency but also examines ports’ capacity utilization. Differences in efficiency measures were discussed, with SFA offering valuable insights into strategic improvements by effectively reflecting operational challenges and external factors.